STUDING THE NANOMETIC FEATURES OF COMERCIAL PURE TITANIUM AFTER THERMOCHEMICAL ETCHING - Shanai Al-Bayati ª˒¹, Raghdaa Jassimᴮ˒², Akram Jabur ͨ˒ ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Titanium surface modifying for the implants by chemical and physical methods generally used with the aim of achieving better osseointegration. This study examines the effects of thermochemical treatments on titanium's nanoscale surface. The physical properties of the surface and topography of CPTi are influencing the outcomes of implant surgery. Method: Three implants surface prepared: first group untreated CpTi (control), second group surface modified by etching with H₂SO4 acid within 80Cº thermal application, and 3rd. group surface modified with HCL and 80Cº thermal application during acid etching. The surface characterized by SEM, AFM, and wettability test analysis of data was done by using statistical SPSS v 22 Result: higher roughness 25.1nm shown when etching performed by H2SO4 with 80C heating for 10min, while the surface roughness was 17nm when etched with HCL under same conditions. The wettability test revel increase in hydrophilicity when H2SO4 used for etching and the contact angle reduced to 56.55 degree. Conclusion: thermochemical etching is an effective surface modification technique that can enhance the properties of commercial pure titanium. The modified surface layer results in enhanced surface roughness, and improved wettability. These properties make the material suitable for various industrial and biomedical applications.